Analysis of Intellectual Capital Disclosure Determinants in Annual Report of Indonesian Commercial Banks from 2014 to 2016 - B1034141005, Mega Puspa Angelia (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
The objective of this research is to analyze the level of intellectual capital disclosure in annual reports provided by 50 commercial banks in Indonesia. This research examine the relationship between intellectual capital disclosure as the dependent variable and bank’s characteristics (bank’s size, bank’s age, profitability, and leverage) as independent variable, along with board independence of corporate governance as a control variable.This research used 50 samples of Indonesian commercial banks with annual reports for the period of 2014 – 2016. Sample in this research was selected using random sampling method. Multiple regression analysis used to test 4 hypotheses in this research.The result suggests that information of intellectual capital that provided in the annual report of the 50 commercial banks on average is 66%. Neither of the bank’s age, bank’s size, profitability, and leverage shows positive relationship with the level of intellectual capital disclosure.  Keyword: intellectual capital disclosure, bank’s characteristic, annual report,Indonesia